Ca(2+)-activated Nucleotidase 1, a Novel Target Gene for the Transcriptional Repressor DREAM (Downstream Regulatory Element Antagonist Modulator), Is Involved in Protein Folding and Degradation - Calì, Tito (American Society for Biochemistry and Molecular Biology, 2012)
DREAM is a Ca(2+)-dependent transcriptional repressor highly expressed in neuronal cells. A number of genes have already been identified as the target of its regulation. Targeted analysis performed on cerebella from transgenic mice expressing a dominant active DREAM mutant (daDREAM) showed a drastic reduction of the amount of transcript of Ca(2+)-activated nucleotidase 1 (CANT1), an endoplasmic reticulum (ER)-Golgi resident Ca(2+)-dependent nucleoside diphosphatase that has been suggested to have a role in glucosylation reactions related to the quality control of proteins in the ER and the Golgi apparatus. CANT1 down-regulation was also found in neuroblastoma SH-SY5Y cells stably overexpressing wild type (wt) DREAM or daDREAM, thus providing a simple cell model to investigate the protein maturation pathway. Pulse-chase experiments demonstrated that the down-regulation of CANT1 is associated with reduced protein secretion and increased degradation rates. Importantly, overexpression of wtDREAM or daDREAM augmented the expression of the EDEM1 gene, which encodes a key component of the ER-associated degradation pathway, suggesting an alternative pathway to enhanced protein degradation. Restoring CANT1 levels in neuroblastoma clones recovered the phenotype, thus confirming a key role of CANT1, and of the regulation of its gene by DREAM, in the control of protein synthesis and degradation.